2019
DOI: 10.1515/jbcpp-2019-0257
|View full text |Cite
|
Sign up to set email alerts
|

Adherence behavior assessment of oral antidiabetic medication use: a study of patient decisions in long-term disease management in primary health care centers in Surabaya

Abstract: BackgroundAdherence to medication has an important role in the long-term management of diabetes. The Indonesian Endocrinologist Association found that of the 50% of the entire population who have been diagnosed with diabetes, two-thirds are undergoing therapy and only one-third have been achieving the intended outcomes of the drug therapy. This study aimed to identify patients’ adherence behavior and the root causes of non-adherence.MethodsThis study used a non-experimental mixed-methods approach. A total of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Insurance coverage and medication availability factors were positively associated in four studies from three countries (Indonesia, China, and India). 37 , 38 , 62 Meanwhile, the high medication cost factor was negatively associated in one study in Bangladesh and India. 30 , 52 Healthcare systems determine medication adherence in several ways.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Insurance coverage and medication availability factors were positively associated in four studies from three countries (Indonesia, China, and India). 37 , 38 , 62 Meanwhile, the high medication cost factor was negatively associated in one study in Bangladesh and India. 30 , 52 Healthcare systems determine medication adherence in several ways.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have found that five factors are more dominant in this category. These factors are the level of education, 35 , 36 , 40 , 42 , 52 knowledge about diabetes and its medications, 35 , 42 , 52 , 53 medication availability, 36 , 38 , 62 social support, 31 , 37 , 46 and socioeconomic status. 31 , 32 , 35 , 44 , 46 More than half of the studies in this review found these four factors to be positively associated (n = 16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations